2018
DOI: 10.1002/jcb.26743
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long non‐coding RNA XIST promotes osteosarcoma progression by targeting YAP via miR‐195‐5p

Abstract: The lncRNA XIST (X inactive-specific transcript) is an oncogenic lncRNA that is present in various malignant tumors; however, its role and molecular mechanisms in osteosarcoma (OS) progression remain unclear. In the current study, 40 pairs of OS tissues and matched adjacent non-tumor tissues were collected. qRT-PCR was conducted to investigate the differences in XIST expression in tissues and OS cell lines. The proliferation, invasion, and EMT status of OS cells after transfection were assessed with WST-1 assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 33 publications
4
70
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) are defined as >200 nucleotides in length with limit or without protein‐coding ability . LncRNAs have emerged as important regulators in all aspects of fields of biology through regulation at the chromatin organization, posttranscriptional, and transcriptional levels .…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are defined as >200 nucleotides in length with limit or without protein‐coding ability . LncRNAs have emerged as important regulators in all aspects of fields of biology through regulation at the chromatin organization, posttranscriptional, and transcriptional levels .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with lowly expressed of XIST group, the group of highly expressed has shorter overall survival in OS. 25,26 In this research, we found that NCRNA00173 was down-regulated in OS tissues and notably relevant with TNM stage and metastasis. Meanwhile, the OS and average survival time of low NCRNA00173 expression ware shorter than high NCRNA00173 expression within 5 years.…”
Section: Discussionmentioning
confidence: 60%
“…[17][18][19] Accumulating evidence suggested that lncRNAs are deregulated in most, if not all, types of human diseases, including tumours, cardiovascular diseases, autoimmune diseases and congenital abnormalities. [20][21][22][23][24] Mechanistically, lncRNAs modulate gene expression at transcriptional and post-transcriptional levels and participate in the regulation of a plethora of molecular, cellular and tissue processes, including DNA synthesis, chromatin modification, cell proliferation, apoptosis, differentiation and organ development. [25][26][27][28] Emerging evidence also suggested that lncRNAs could participate in the pathogenesis of orthopaedic diseases, such as intervertebral disc degeneration, osteoporosis, osteosarcoma and osteoarthritis.…”
Section: Long Non-coding Rnas (Lncrnas) Are a Group Of Non-codingmentioning
confidence: 99%